The Histopathologic Evaluation of Diagnostic Procedures in Nail Melanoma - Dika, Emi; Starace, Michela; Alessandrini, Aurora; Patrizi, Annalisa; Baraldi, Carlotta; Misciali, Cosimo; Fanti, Pier Alessandro; Waśkiel-Burnat, Anna; Rudnicka, Lidia; Piraccini, Bianca Maria (Dermatology Practical & Conceptual, 2023)
Introduction: The diagnostic delay in nail melanoma (NM) has been repeatedly emphasized. It may be related to both clinical misinterpretations and to errors in the bioptic procedure.Objectives: To assess the efficacy of histopathologic examination in different diagnostic biopsies in NM.Methods: We retrospectively investigated the diagnostic procedures and histopathologic specimens referred to the Laboratory of Dermatopathology for the clinical suspicion of NM from 2006 to January 2016.Results: Eighty-six nail histopathologic specimens were analysed consisting in 60 longitudinal, 23 punch and 3 tangential biopsies. A diagnosis of NM was performed in 20 cases, benign melanocytic activation in 51 cases and melanocytic nevi in 15 patients. Longitudinal and tangential biopsy were diagnostic in all cases, regardless of the clinical suspicion. Nail matrix punch biopsy instead was not diagnostic in most of the cases (13/23 specimens).Conclusions:  In the presence of an NM clinical suspicion, longitudinal biopsy is recommended (lateral or median) because it provides exhaustive information on the characteristics of melanocytes’ morphology and distribution in all the components of the nail unit. Tangential biopsy, recently encouraged by expert authors due to the optimal surgical outcome, in our experience gives incomplete information on tumor extension. Punch matrix biopsy gives limited evidence in the diagnosis of NM.